'Why do these people's opinions matter?' Positioning known referents as unnameable others. (June 2013) - Jackson, Clare
The way we refer to third parties in talk is one means through which relationships between speaker, recipients and referents are made relevant. A range of referring expressions is available and any number of expressions might correctly refer to a referent. One guide to selection is the preference for achieving recognition and the default practice is, where possible, to use a name. This conversation analytic article describes a practice that does not fit the default pattern. In this practice, speakers select a broad social category (typically gendered, e.g. guy, woman, but not always, e.g. people ) when a recognitional form could (and perhaps, ought to) have been used. Despite the designed selection of a categorical form, the referent(s) remains recognitional. For example, in one extract, a mother in conversation with her teenage daughter refers to a collective made up of her former husband and his girlfriend as 'these people'. The daughter has no difficulty working out who 'these people' are and recognizes it as a reference to her father and stepmother. I show that this designedly categorical formulation often contributes to hostile action by distancing the referent(s) from parties to the interaction – making the referent(s) unnameable and not connected to the speaker and recipient. The role of demonstrative pronouns – this, that, these – are discussed in relation to constructing social distance between speakers, recipients and referents.